2009
DOI: 10.1177/0218492309102609
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Outcome of Coronary Artery Bypass Grafting and Coronary Endarterectomy

Abstract: To compare hospital mortality and postoperative complications in patients with severe coronary artery disease undergoing coronary artery bypass grafting with or without coronary endarterectomy, 100 consecutive patients were divided into 2 groups of 50 patients each. Group 1 had coronary endarterectomy, and group 2 had no coronary endarterectomy. There were 87 men and 13 women, with a mean age of 54.79 +/-7.8 years; 48% had stable angina. The right coronary artery was endarterectomized in 22 patients, the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Based on these results, most authors have concluded that CE is a suitable method in the treatment of severely diseased coronary arteries for which complete revascularization cannot be obtained otherwise [ 2 12 ]. Prospective randomized trials can provide an accurate and unbiased comparison of outcomes; however, the only well-designed prospective randomized trial so far published comparing CABG with or without CE had a sample size of 50 for each group [ 13 ]. The low sample size of this study resulted in a low statistical power, and therefore the study could not show a difference between either the short-term or long-term outcomes associated with CE and CABG [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, most authors have concluded that CE is a suitable method in the treatment of severely diseased coronary arteries for which complete revascularization cannot be obtained otherwise [ 2 12 ]. Prospective randomized trials can provide an accurate and unbiased comparison of outcomes; however, the only well-designed prospective randomized trial so far published comparing CABG with or without CE had a sample size of 50 for each group [ 13 ]. The low sample size of this study resulted in a low statistical power, and therefore the study could not show a difference between either the short-term or long-term outcomes associated with CE and CABG [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Looking at our cohort of patients referred for CABG, more than 75% of patients had DM, hypertension and dyslipidemia, and even more, 10% of them had previous PCI. With more diffuse CAD, complete revascularization becomes an issue with conventional CABG, hence the need to adopt alternative surgical techniques such as coronary endareterctomy (CE) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Schimitto et al, reported an early mortality rate of 5% in 104 patients, with most common vessel being endactectomized was the RCA (55%) followed by LAD (35%) [22]. However, Abid et al, demonstrated an early mortality rate of 2% (cases: RCA endarterectomy 44%, and LAD endarterectomy 42%), and there was no statistical difference in mortality when compared with CABG alone [8]. Moreover, Silberman et al, showed a mortality rate with LAD endarterectomy reaching 10%, compared with non-LAD endarterectomy (4%) and CABG alone (3%) with significant p value of 0.001 [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation